Fashion and cultural studies. - Kaiser, Susan B.; Green, Denise Nicole (Bloomsbury Visual Arts, 2021)
Bridging theory and practice, this accessible text considers fashion from both cultural studies and fashion studies perspectives, and addresses the growing interaction between the two fields. Kaiser and Green use a wide range of cross-cultural case studies to explore how race, ethnicity, class, gender and other identities intersect and are produced through embodied fashion. Drawing on intersectionality in feminist theory and cultural studies, 'Fashion and Cultural Studies' is essential reading for students and scholars.